SIGNAL TRANSDUCTION. Membrane potential modulates plasma membrane phospholipid dynamics and K-Ras signaling. - Zhou, Y.; Wong, C.O.; Cho, K.J.; van der Hoeven, D.; Liang, H.; Thakur, D.P.; Luo, J.; Babic, M.; Zinsmaier, K.E.; Zhu, M.X.; Hu, H.; Venkatachalam, K.; et al. (Science, 2015)
Plasma membrane depolarization can trigger cell proliferation, but how membrane potential influences mitogenic signaling is uncertain. Here, we show that plasma membrane depolarization induces nanoscale reorganization of phosphatidylserine and phosphatidylinositol 4,5-bisphosphate but not other anionic phospholipids. K-Ras, which is targeted to the plasma membrane by electrostatic interactions with phosphatidylserine, in turn undergoes enhanced nanoclustering. Depolarization-induced changes in phosphatidylserine and K-Ras plasma membrane organization occur in fibroblasts, excitable neuroblastoma cells, and Drosophila neurons in vivo and robustly amplify K-Ras-dependent mitogen-activated protein kinase (MAPK) signaling. Conversely, plasma membrane repolarization disrupts K-Ras nanoclustering and inhibits MAPK signaling. By responding to voltage-induced changes in phosphatidylserine spatiotemporal dynamics, K-Ras nanoclusters set up the plasma membrane as a biological field-effect transistor, allowing membrane potential to control the gain in mitogenic signaling circuits.